Accidents of influence : writing as a woman and a Jew in America - Rosen, Norma (Albany : State University of New York Press, 1992)
Annotation Examines the relationship of post-Holocaust writers to their work in terms of subject, language, imagery, and facing up to the task of writing in a post-Holocaust era. The 32 previously published essays include personal accounts of being a Jewish woman writer in America, and critiques of literature. No index or bibliography. Paper edition (unseen), $10.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Print version record.
eBooks on EBSCOhost
Keywords: Jewish women -- United States -- Literary collections; Jews -- Literary collections; Juives -- États-Unis -- Anthologies; Juifs -- Anthologies; LITERARY COLLECTIONS -- Essays; Jewish women; Jews; United States; UNITED STATES; Electronic books; Literary collections